Effect of Wine Closures on the Aroma Properties of Chardonnay Wines after Four Years of Storage - Liu, N.; Song, Y.-Y.; Dang, G.-F.; Ye, D.-Q.; Gong, X.; Liu, Y.-L. (South African Journal of Enology and Viticulture, 2016)
The effects of wine closures on the sensory properties and aroma profiles of fresh Chardonnay wines were evaluated after four years of bottle storage. Natural cork closure, technical cork closure, Nomacorc light, Nomacorc classic and Nomacorc premium were investigated. Among these wines sealing with different closures, the physicochemical parameters of the wine samples showed no significant differences, except that of the free and total sulphur dioxide. Nomacorc light with the highest OTR (oxygen transition rate) had the least residual free sulphur dioxide. Most of volatiles were generally stable, and seven compounds (acetoin, 1-butanol, 2-phenylethanol, 1-pentanol, (Z)-3-hexen-1-ol, 2-nonanol and ethyl decanoate) were significantly affected by the wine closures. The sensory analysis revealed that cork closures preserved more fruity/flowery characters of the fresh wines after four years’ storage, as well as cork-tainted off-flavour. Two synthetic closures (Nomacorc light, Nomacorc classic) imparted some grilled attributes to the wines. Nomacorc premium highly reserved the fruity/flowery flavour without cork contamination or oxidised toasted characters.